2008
DOI: 10.1016/j.devcel.2008.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Role of EVERGREEN in the Development of the Cymose Petunia Inflorescence

Abstract: Plants species diverge with regard to the time and place where they make flowers. Flowers can develop from apical meristems, lateral meristems, or both, resulting in three major inflorescence types known as racemes, cymes, and panicles, respectively. The mechanisms that determine a racemose architecture have been uncovered in Arabidopsis and Antirrhinum. To understand how cymes are specified, we studied mutations that alter the petunia inflorescence. Here we show that EVERGREEN (EVG) encodes a WOX homeodomain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
87
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(90 citation statements)
references
References 31 publications
3
87
0
Order By: Relevance
“…In this respect, it is telling that petunia plants mutated in the ortholog of S not only fail to branch, but also mostly lack flowers altogether (23). Because meristem termination in sympodial plants is synonymous with flowering (13), another potential modulator of branching is the mobile flowering inducer and termination signal, florigen, encoded in tomato by the SINGLE FLOWER TRUSS (SFT) gene (24).…”
Section: Discussionmentioning
confidence: 99%
“…In this respect, it is telling that petunia plants mutated in the ortholog of S not only fail to branch, but also mostly lack flowers altogether (23). Because meristem termination in sympodial plants is synonymous with flowering (13), another potential modulator of branching is the mobile flowering inducer and termination signal, florigen, encoded in tomato by the SINGLE FLOWER TRUSS (SFT) gene (24).…”
Section: Discussionmentioning
confidence: 99%
“…When mutated, floral identity is delayed (s mutant) or never achieved (an mutant), causing SIM overproliferation and highly branched inflorescences (Lippman et al 2008;Park et al 2012). Parallel functions for S and AN in pepper and petunia (Lippman et al 2008;Rebocho et al 2008;Souer et al 2008;Cohen et al 2014) suggest they can serve as specific markers of meristem maturation schedules. To obtain a more precise assessment of when and how maturation schedules vary, we performed in situ hybridization of S and AN in TM through FM stages in S. lycopersicum, S. peruvianum, S. prinophyllum, and N. benthamiana ( Fig.…”
Section: Heterochronic Expression Of Two Key Meristem Maturation Regumentioning
confidence: 99%
“…Recent works have shown that alterations in the spatial and temporal expression patterns of a few regulatory genes generate a dramatic divergence of inflorescence form (Prusinkiewicz et al, 2007;Lippman et al, 2008;Rebocho et al, 2008). In petunia and tomato (Solanum lycopersicum), which form cymose inflorescences, fine tuning of spatial and temporal distribution of EVERGREEN (EVG) and Compound inflorescence (S) expressions is crucial to form the cymose inflorescence.…”
Section: Apo1 Promoter and Rice Inflorescence Formmentioning
confidence: 99%